Comparative efficacy between retrograde intrarenal surgery with vacuum-assisted ureteral access sheath and minimally invasive percutaneous nephrolithotomy for 1–2 cm infectious upper ureteral stones: a prospective, randomized controlled study - Tang, Qing-lai; Liang, Ping; Ding, Ye-fei; Zhou, Xing-zhu; Tao, Rong-zhen (Frontiers in Surgery, 2023)
Objective To observe the efficacy and safety of retrograde intrarenal surgery combined with vacuum-assisted ureteral access sheath (V-UAS) and minimally invasive percutaneous nephrolithotomy (MPCNL) in patients with 1-2 cm infectious upper ureteral stone. Patients and Methods A total of 173 patients with 1-2 cm infectious upper ureteral stone were prospectively randomized into two groups. Eighty-six in the V-UAS group and 87 cases as control in the MPCNL group. The SFRs at different times (Postoperative 1 day, 2nd week and 4th week) was considered as the primary outcome of the study. The secondary end points were operative time, postoperative hospital stay and operative complications. Results There was no obvious difference between two groups in patients’ demographics and preoperative clinical characteristics (all P > 0.05). Postoperative data showed that the SFR at postoperative 1 day in the V-UAS group was significantly lower than that in the MPCNL group (73.2% vs. 86.2%, P = 0.034). However, there was no statistical significance between two groups in SFRs during postoperative 2 weeks and 4 weeks (All P > 0.05). The levels of WBC, CRP and PCT were all significant lower in the V-UAS group than those in the MPCNL group at the postoperative 24 hours and 48 hours (all P < 0.05). Postoperative complications included fever (≥38.5℃), bleeding, pain and urosepsis. In terms of the rates of fever, pain and urosepsis, MPCNL group were all significantly higher than those in the V-UAS group (10.3 vs. 2.4%, P = 0.031; 14.9 vs. 2.4%, P = 0.003; 4.6 vs. 0.0%, P = 0.044; respectively). No significant difference was found between two groups in bleeding. Meanwhile, postoperative hospital stay in the V-UAS group was more shorten than that in the MPCNL group (3.7 vs. 5.9 days, P < 0.001). Conclusions Our study showed that RIRS with V-UAS, a new partnership to treat 1-2 cm infectious upper ureteral stones, was satisfying as it achieved a high SFR rate and a low rate of infectious complications. This method was safe and reproducible in clinical practice.